(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2024)
This study rigorously investigates how STEM-based learning can influence the sustainability actions of senior high school students. Three indicators of sustainable actions were synthesized from several indicators: action competence, past, present, and future action, and the impact of the actions. The study, involving 148 students divided into two experimental and two control classes, revealed a significant result in the past, present, and future action indicators. Secondary data was obtained from unstructured interviews with teachers and students to provide insight into how learning can influence students’ sustainability actions. These results offer valuable insight into the potential of STEM-based education to influence certain aspects of students’ sustainable actions positively.